Teleki Pál és a térkép - Bassa, László (Tér és Társadalom, 1990)
The activity of Count Paul Teleki (1879-1941), the reknown Hungarian geographer, can be observed from a dual viewpoint. The first one is inseparable from the historical period in which he lived. His career started in the beginning of our century when he was inspired by the lively economic, political and spiritual atmosphere of the Austro-Hungarian Monarchy. Further events also occurred during his lifetime, namely the First World War, the collapse of the empire and the subsequent revolutions, two decades of counter-revolution and the "success" of, policy aiming at the restoration of some of the territories Hungary had lost after the war, finally the drift of the country towards the Second World War, were the crueial points determining his activity. The second aspect is a more subjective one and is related to Teleki's far-reaching personal ambitions, since.in various periods of his life, although to a different extent, he acted as a politician, a scolar and a teacher. As a politician (among others, prime minister of Hungary in 1920 and from 1939 to 1941) he extensívely used maps, compiled by himself, when arguing over different issues, especially during the negotiations of the Trianon peace treaty and in the revisionist campaign, involving ethnic maps based on the 1910 census of the Monarchy (the famous Carte rouge). For Teleki the scholar maps were primarily the tools for geographic synthesis. He considered analytic maps mere "mapped statistics" still indispensable for the compilation of more sophisticated types of maps: the complex and synthetic ones in a contemporary sense. He was an outstanding representative of regionalism in geography, which, instead of searching for global regularities of phenomena, aimed at detailed and retrospective diagnoses of certain segments on the surface of Earth (regions, landscape units etc.) and of relationships between them, putting a strong emphasis on their uníqueness. According to Teleki, location and distribution of phenomena shown on maps should primarily reveal this interrelationship. Paul Teleki, university professor of economic geography had a slogan, written as a motto to his book, the Geographical bases of economic life, a transcript of his lectures by pupils: "Always study with a map by your side! Learn from the map! Practise map reading, not just with one map but with several types of maps!". He brought up a generation of geographers who were closely attached to cartography, too.